Contributions of neuropsycededogogy to the pedagogical follow-up of the student with mental disability (Revista Educação, Artes e Inclusão, 2023)
The inclusion of mentally handicapped people is among the greatest challenges of contemporary Brazilian education. The school, used to working with a learning model that does not consider human diversity, finds it difficult to adapt to the specificities of students with mental disabilities. Through an exploratory research with a qualitative approach, theoretical contributions were gathered from the fields of special education, neuroscience, neuropsychopedagogy, pediatrics and psychology to understand the implications of mental disability and the possible ways in which the neuropsychopedagogue can assist in the teaching-learning process of students who have such a deficiency. According to several authors, neuropsychopedagogy corresponds to a field of knowledge of extreme importance for the understanding of the brain mechanisms that lead to learning, the elaboration of diagnoses about the origins of learning problems and the performance of assertive pedagogical interventions. The investigative path allowed us to consider the role of neuropsychopedagogy as essential for the growth of self-confidence and motivation for the learning of the mentally disabled.
Keywords: learning; mental deficiency; Neuropsychopedagogy